Development of Picture Card Media as a Geography Learning Media - Ulin Niam (Journal of Social Knowledge Education (JSKE), 2023)
Purpose of the study: Methodology: This type of research is development research (R&D). The stages of R&D research include potentials and problems, data collection, product design, design validation, design revisions, product trials, product revisions, usage trials. The variables of this study: the level of use of media in schools, the level of student activity during learning and student learning outcomes. Collection techniques include questionnaires and documentation. Main Findings: The results of the research on the development of picture card media have a media feasibility level of 46 and material 45. From the total expert validation score the material with criteria is feasible for use in school learning. While the teacher's media validation has a score of 47 and a score of 48 with feasible criteria. At the level of media use based on research results, it has a score of 62.64 with sufficient criteria. While the results of student activity have a student activity level with a total average score of 2.27 and experience an increase in the second meeting with an average activity level of 2.57. Student activities using picture card media experienced an average increase of 0.3 and had an average total score between the first and second activities on the high criterion with a score of 2.42. In these results the level of effectiveness in the use of picture card media has high criteria which can be said to be effective. Novelty/Originality of this study: In developing visual media, picture media is an effective medium to develop. Because the level of use of picture media is in high criteria, the level of use of picture media is said to be effective. The suggestion in this study is to increase existing facilities. To meet the needs of visual media, picture media is media effectively developed.